2007
DOI: 10.1111/j.1745-7254.2007.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the physiological relevance of in vitro cancer preventive activities of phytochemicals

Abstract: There is growing interest in the ability of phytochemicals to prevent chronic diseases, such as cancer and heart disease. However, some of these agents have poor bioavailability and many of the in‐depth studies into their mechanisms of action have been carried out in vitro using doses which are unachievable in humans. In order to optimize the design of chemopreventive treatment, it is important to determine which of the many reported mechanisms of action are clinically relevant. In this review we consider the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 252 publications
(190 reference statements)
1
76
1
Order By: Relevance
“…Concentrations of phytochemicals were 3 Amol/L curcumin, 10 Amol/L 3,3 ¶-diindolylmethane (DIM), 8 Amol/L epigallocatechin gallate (EGCG), 2.5 Amol/L genistein, and 30 Amol/L indole-3-carbinol (I3C). Comparable serum concentrations for curcumin (1.77 F 1.87 Amol/L), DIM (20 Amol/L), EGCG (0.29 -7.7 Amol/L), genistein (2.5 F 1.6 Amol/L), and I3C (28 Amol/L) were detected in humans and/or animal models (4,5).…”
Section: Introductionmentioning
confidence: 98%
“…Concentrations of phytochemicals were 3 Amol/L curcumin, 10 Amol/L 3,3 ¶-diindolylmethane (DIM), 8 Amol/L epigallocatechin gallate (EGCG), 2.5 Amol/L genistein, and 30 Amol/L indole-3-carbinol (I3C). Comparable serum concentrations for curcumin (1.77 F 1.87 Amol/L), DIM (20 Amol/L), EGCG (0.29 -7.7 Amol/L), genistein (2.5 F 1.6 Amol/L), and I3C (28 Amol/L) were detected in humans and/or animal models (4,5).…”
Section: Introductionmentioning
confidence: 98%
“…Cyclin D1 over-expression has been linked with breast, esophageal, head, neck, and prostate cancers (77). There are always concerns about how to interpret in vitro studies because of issues related to physiologically relevant concentrations and bioavailability (94,95).…”
Section: Inflammation-sincementioning
confidence: 99%
“…However, the marked decrease in proliferative capacity combined with a decreased nuclear signalling pool of β-catenin and increases in the tumour suppressor E-cadherin warrants further investigation regarding the potential of this combination. A number of studies have clearly demonstrated that I3C is biologically active in animals and humans [10] so it will be crucial to determine whether the effects reported here can also be replicated in vivo and most importantly, within a clinical context. …”
Section: Discussionmentioning
confidence: 99%
“…I3C is currently in clinical trial for treatment of recurrent respiratory papillomatosis [5,6] and cervical intraepithelial neoplasia [7,8] and has been shown to be well tolerated at doses up to 400mg/day [9]. Pharmacokinetic studies of I3C disposition have revealed systemic doses of up to 170μmol/L in tissue [10], which equates with in vitro efficacy particularly in the liver [11,12] which along with lymph nodes [13,14], is the major site for colorectal metastasis. I3C has been shown to exhibit both anti-proliferative and anti-invasive potential [15] via a variety of mechanisms, including up-regulation of E-cadherin and β-catenin at the cytoplasmic membrane [16,17], concurrent with down-regulation of nuclear β-catenin levels.…”
Section: Introductionmentioning
confidence: 99%